Full Automation and Control System Based on IoT in a Greenhouse (Case Study: Faculty of Agriculture, Malikussaleh University - M Ishlah Buana Angkasa; Rizal Tjut Adek; Said Fadlan Anshari (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
This study aims to develop a full automation and control system based on the Internet of Things (IoT), implemented in a greenhouse to support real-time monitoring of temperature, soil moisture, and water levels in the tank. The system is designed using the ESP32-WROOM microcontroller as the core for data communication with various sensors, including the DHT22 sensor for air temperature and humidity, a soil moisture sensor for soil moisture, and a JSN-SR04T sensor for water level. The developed system connects to Firebase as a cloud data platform, enabling remote monitoring via a specially designed mobile application. Testing shows that the system works efficiently in supporting automated plant growth, reducing manual intervention, and increasing productivity. This system allows students and faculty in the Faculty of Agriculture at Malikussaleh University to more easily conduct research and teaching activities related to modern agricultural technology.